2018
DOI: 10.1002/ldr.2971
|View full text |Cite
|
Sign up to set email alerts
|

Perennial biomass production from marginal land in the Upper Mississippi River Basin

Abstract: Marginal land is considered promising for biomass production. However, understanding on biomass crop growth and total biofuel production from this land type is very limited. This study evaluated potential production of switchgrass (Panicum virgatum) and Miscanthus (Miscanthus × giganteus) on marginal lands in the Upper Mississippi River Basin. A soil and water assessment tool model with detailed representation of marginal lands and their suitability for growth of the 2 grasses was setup. Marginal land was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
0
10
3
Order By: Relevance
“…Although some have argued that land-use change for the production of energy crops may increase GGEs [6], this claim is essentially valid only for first-generation corn-based ethanol production, and for the cases where forest and grassland are being diverted to biofuel production. A viable alternative to achieve a large proportion of the IPCC target of 7 million km 2 without extensive land-use change is the utilisation of second-generation lignocellulosic feedstocks, which are non-food resources that can be produced with high yields in marginal land [7]—abandoned agricultural land, degraded land, reclaimed land and wasteland. Furthermore, a large-scale industry based on lignocellulose also represents a more sustainable alternative to petrochemical pathways, as released carbon is balanced by photosynthetic capture [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although some have argued that land-use change for the production of energy crops may increase GGEs [6], this claim is essentially valid only for first-generation corn-based ethanol production, and for the cases where forest and grassland are being diverted to biofuel production. A viable alternative to achieve a large proportion of the IPCC target of 7 million km 2 without extensive land-use change is the utilisation of second-generation lignocellulosic feedstocks, which are non-food resources that can be produced with high yields in marginal land [7]—abandoned agricultural land, degraded land, reclaimed land and wasteland. Furthermore, a large-scale industry based on lignocellulose also represents a more sustainable alternative to petrochemical pathways, as released carbon is balanced by photosynthetic capture [8].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, studies quantifying the relative contribution of upstream regions to downstream flow variability, separating out the role of climate and land use and attributing potential changes to local/regional driving factors (e.g., Du et al, 2018 ; Frans et al, 2013 ; Tao et al, 2014 ; Wise et al, 2017 ), may erroneously delineate targeted hydrologic management locations (e.g., Figure 4b ) if surface depression storage is not considered in model simulations. This may lead to serious implications for socio-hydrologic modeling involving crop yield, irrigation requirements, and sustainable alternatives in agroecosystems to support human demand ( Feng et al, 2018 ; Srinivasan et al, 2010 ; Yaeger et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at the continental scale, it has been reported that Africa, Europe, and South America have 66-481 M ha of potential marginal land for biomass cropping under different land-cover scenarios, which equates to 10-55% of the global liquid fuel consumption [20]. On the other hand, at the local level, Feng et al [8,21] employed 30-m resolution data for estimating total bioenergy resources at the watershed and regional scales. Marginal land suitability in the Upper Mississippi River Basin for biofeedstock crops was obtained, and their results demonstrated that 60% of the marginal land was suitable for the growth of energy crops.…”
Section: Introductionmentioning
confidence: 99%